Wewe Gombel dan Abuh: Komparasi Cerita Mistis-Pedagogis Masyarakat Kaliputih Jawa Tengah dan Silat Hulu Kalimantan Barat: Wewe Gombel and Abuh: A Comparison of the Mystic-Pedagogical Stories of the Kaliputih Villagers in Central Java and Silat Hulu in West Kalimantan - Yudono, Kristophorus Divinanto Adi; Margareta, Yustina Yuyu; Widiyanto, Nugro (Journal of Literature and Education, 2025)
The objectives of this research include describing the mystical content of the Wewe Gombel ghost story, which is believed by the people of Kaliputih Wonosobo Village, Central Java, and Abuh Ghost that is believed by the people of Bantansari Silat Hulu Village, West Kalimantan, and comparing the pedagogical content contained in the two ghost stories in the two areas. The research method is qualitative with ethnographic techniques. The data source comes from the speech of the people of Bantansari Village, Silat Hulu, West Kalimantan, and the speech of the people of Kaliputih Village, Wonosobo, Central Java. Data collection techniques are carried out by interviews and documentation. The results of the study showed that there was a pedagogical content in the story of the ghost of Wewe Gombel which was believed by the people of Wonoso, Central Java, and the story of the ghost of Abuh which was believed by the people of Silat Hulu, West Kalimantan. These two ghost stories have pedagogical content in the form of invitations and invitations for children to obey parental advice. The educational value behind this ghost story is the attitude teaching which is spoken along with the ghost story that develops in society.